Marital decision-making, satisfaction with marital decision-making, and marital satisfaction - Oberes, Jemima Camacho; Ocbena, Mia Florence Villareal (2006.)
This study examined the relationship of marital decision making, satisfaction with marital decision-making and marital satisfaction.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Marriage -- Decision-making.